Role of Cryopreserved Placenta Extract in Prevention and Treatment of Paracetamol-Induced Hepatotoxicity in Rats - Koshurba, Illia V; Chyzh, Mykola O; Hladkykh, Fedir V; Komorovsky, Roman R; Marchenko, Mykhailo M (Scripta Medica, 2023)
Background/Aim: Drug-induced liver injury is one of the major causes of acute liver failure. Under current circumstances of the pandemic of COVID-19 pandemic, the use of paracetamol which has a proven hepatotoxic effect has increased. This prompts the search for novel agents with hepatoprotective properties. The purpose of this article was to evaluate the hepatoprotective activity of cryoextract of the placenta (CEP) on the model of paracetamol-induced hepatitis. Methods: The study was performed on 28 male rats. Acute drug liver damage was modelled by intragastric administration of paracetamol twice at a dose of 1250 mg/kg. Results: The development of paracetamol-induced hepatitis in rats was accompanied by a 71.3 % increase (p < 0.001) in the content of active products of thiobarbituric acid (TBA-AP) in liver homogenates as compared with intact animals. Besides, there was a 2.1-fold (p < 0.001) increase of ALT activity, a 58.8 % increase (p < 0.001) of AST activity and a 4.2-fold (p < 0.001) increase of the concentration of total bilirubin as compared with intact rats. The use of cryopreserved placenta extract showed significant hepatoprotection in a rat model of paracetamol-induced hepatitis. This was demonstrated by a 2.3-fold (p < 0.01) increase of the antioxidant-prooxidant index, a significant (p < 0.001) decrease of activity of ALT (by 44.0 %) and AST (by 29.6 %), as well as by a decrease of direct bilirubin level by 52.5 % (p < 0.001) in animals treated with CEP as compared with rats without treatment. Conclusion: The development of acute paracetamol-induced hepatitis in rats was associated with activation of lipid peroxidation processes in liver tissues, while CEP showed marked hepatoprotective activity in paracetamol-induced hepatitis in rats.